Análise do papel de Organizações Transnacionais da Sociedade Civil no desenvolvimento de Redes Comunitárias de Internet a partir do caso do Bairro Novo, Penalva, MA - Aguiar, João Paulo de Vasconcelos (2021)
During the COVID-19 pandemic, the Internet has been an essential tool for activities ranging from work to education and access to public services. Meanwhile, 46% of the world’s population is still not connected, especially in rural and remote areas. Telecommunications services are expanding at a slow rate, and the traditional model of access provision through telecommunications conglomerates appears to be insufficient for the digital inclusion of people living in these areas. Meanwhile, communities that need the Internet are developing an alternative connectivity model known as community networks. This model is seen by transnational civil society organizations as an innovative and complementary solution for digital inclusion, and they have supported the development of such networks globally. This article aims to analyze how these organizations promote the community networks model through the study of a network developed by a community in the city of Penalva, in the State of Maranhão, Brazil. In order to develop this study, documents, reports, and news stories from these organizations are analyzed, as well as articles studying community networks as an alternative to digital inclusion. This study also analyzes publications about the network in Penalva, as well as interviews with stakeholders in its development process. Among the many ways in which these organizations support the development of community networks are the financing of these initiatives, the training of communities, and their participation in policy and regulation processes in order to foster the existence of such networks